2016
DOI: 10.3390/bioengineering3040031
|View full text |Cite
|
Sign up to set email alerts
|

Focused Screening of ECM-Selective Adhesion Peptides on Cellulose-Bound Peptide Microarrays

Abstract: The coating of surfaces with bio-functional proteins is a promising strategy for the creation of highly biocompatible medical implants. Bio-functional proteins from the extracellular matrix (ECM) provide effective surface functions for controlling cellular behavior. We have previously screened bio-functional tripeptides for feasibility of mass production with the aim of identifying those that are medically useful, such as cell-selective peptides. In this work, we focused on the screening of tripeptides that se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 38 publications
0
10
0
Order By: Relevance
“…We have also reported the sequence-function relationships of various peptides by analysis based on physical characteristics of amino acids, positions of amino acids, and peptide activity data. [25][26][27][28][29] For example, by analyzing an amino acid substitution library, we revealed that the cell death-inducing peptide (WELVVLGKL), which works inside cells, has some rules related to the properties of amino acids with peptide activity. The amino acid substitutions at the second and fourth residues from the N-terminus showed higher activity, especially when the residues were hydrophilic amino acids.…”
Section: Cyclic Peptide Screening and Optimization Methods Have Beenmentioning
confidence: 99%
See 4 more Smart Citations
“…We have also reported the sequence-function relationships of various peptides by analysis based on physical characteristics of amino acids, positions of amino acids, and peptide activity data. [25][26][27][28][29] For example, by analyzing an amino acid substitution library, we revealed that the cell death-inducing peptide (WELVVLGKL), which works inside cells, has some rules related to the properties of amino acids with peptide activity. The amino acid substitutions at the second and fourth residues from the N-terminus showed higher activity, especially when the residues were hydrophilic amino acids.…”
Section: Cyclic Peptide Screening and Optimization Methods Have Beenmentioning
confidence: 99%
“…A cell adhesion assay was conducted on SPOT arrays according to a previously described method with minor modifications 27,28 . Each spot from the synthesized peptide array, corresponding to a different peptide, was punched out as a disk and embedded in a 96‐well plate.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations